Liquid crystal emulsion compound for promoting toner permeation as well as preparation method and application of liquid crystal emulsion compound
By preparing a liquid crystal emulsified complex for hair dye cream, the problem of low penetration of dye coupling agents in the existing hair dye cream is solved, and the brightness, saturation and durability of the hair color after dyeing the hair are greatly improved.
Patent Information
- Application Number
- CN202411324179.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The cationic emulsifiers and monoglycerides used in existing hair dye creams cause structural changes in the dye coupling agent before penetration into the inside of the hair, resulting in lighter color, low saturation and poor gloss after dyeing.
A liquid crystal emulsifier is used to respond to the esterxidized reaction in the reaction kettle of the hydroponic in the water -containing reaction kettle through the hydrolyzed and sodium sodium sulfate, sodium sulfate sulfate, and oxic acid MEA salt/ The ammonia salt mixed mixing is used to prepare lotion and cream, forming a stable and uniform LCD phase to promote the penetration of color powder.
It significantly enhances the brightness, saturation and durability of the hair color after the dyeing, the paste is delicate, the pearl is bright, and the viscosity is moderate.
Smart Images

Figure CN119345069A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of personal care products, and in particular to a liquid crystal emulsified composite for promoting toner penetration, and a preparation method and application thereof. Background Art
[0002] As people's requirements for appearance modification increase, hair dyeing is loved by people as the most effective way to modify hair. On the one hand, hair dyeing can modify white hair caused by genetics, diseases, aging and other problems to make it look younger and more energetic; on the other hand, hair dyeing can also be used as a means for young people to show their personality and pursue fashion. Hair dyeing mainly involves the alkaline components in the hair dye opening the hair scales, and the small molecule precursors of the dye, the dye coupling agent and the oxidant penetrate into the cortex of the hair to undergo an oxidative condensation reaction. The small molecule precursors of the dye are oxidized and condensed into macromolecules with the dye coupling agent, which stay in the epidermis and cortex of the hair fiber and show the target color. During the dyeing process, the emulsifiers and some solvents contained in the hair dye have a penetrating effect on the dye coupling agent. The difference in emulsifiers will cause significant differences in the color performance of the dyed hair.
[0003] At present, most of the permanent hair dyes on the market use cationic quaternary ammonium salts such as C18 alkyl trimethyl ammonium chloride and non-ionic monoglycerol stearate, fatty alcohol polyether and other emulsifiers. After the hair dye containing dye coupling agent is mixed with the oxidant, the emulsion breaks and becomes thinner. At the same time, under the catalysis of the strong oxidant, the cationic emulsifier will react with the dye coupling agent of the system, causing the dye coupling agent to undergo structural changes before penetrating into the hair. The dye molecules become larger, resulting in a decrease in permeability, which is manifested as a lighter color, low saturation, and poor gloss after dyeing. At the same time, alkyl cationic emulsifiers and monoglycerides are not conducive to forming a delicate paste in the hair dye system. Usually, the hair dye containing cationic emulsifiers and monoglycerides is pale and hard, with poor appearance and is not conducive to mixing with oxidants, affecting use. Summary of the invention
[0004] In view of the defects of the prior art, the present invention prepares a liquid crystal emulsified composite, which is used to prepare emulsions and creams, can form a stable and uniform liquid crystal phase, and can improve the brightness, saturation and durability of the color of dyed hair.
[0005] In order to achieve the above purpose, the present invention solves the technical problem by adopting the following technical solutions:
[0006] In one aspect, the present invention provides a method for preparing a liquid crystal emulsified composite for promoting toner penetration, the preparation method comprising the following steps:
[0007] S1. Under inert gas, oleyl alcohol polyether and P2O5 are esterified in a water-containing reactor at 95 to 125 ° C for 2 to 4 hours, wherein the water is 2% of the total reactants by mass;
[0008] S2. After the esterification reaction is completed, hydrolyze at 70-85° C. for 0.5-2 h to obtain oleyl alcohol polyether phosphate;
[0009] S3. Mix the oleyl alcohol polyether phosphate, sodium oleyl alcohol polyether sulfate, sodium stearyl alcohol sulfate, and MEA oleate / ammonium salt in a mass ratio of (35-45):(20-30):(5-15):(20-30), heat and stir evenly to obtain a liquid crystal emulsified composite.
[0010] In some embodiments, in step S1, the oleth is one or more of oleth-5, oleth-8, oleth-10, and oleth-20.
[0011] In some of the embodiments, in step S1, oleyl alcohol polyether is first added into a reaction kettle containing water, and then the temperature is raised to 85-120° C. and P2O5 is slowly added thereto, and the addition time is 40-70 min.
[0012] In some of the embodiments, in step S1, the molar ratio of oleyl alcohol polyether to P2O5 is (1.8-2.8):(0.6-1.2).
[0013] In some embodiments, in step S1, the molar ratio of oleyl alcohol polyether to P2O5 is 2.4:0.9.
[0014] In some embodiments, in step S3, the mass ratio of oleth phosphate, sodium oleth sulfate, sodium stearyl sulfate, and MEA oleate / ammonium salt is 40:25:10:25.
[0015] On the other hand, the present invention also provides a daily chemical product, including the liquid crystal emulsified composite prepared by the above preparation method.
[0016] Specifically, the dosage form of the daily chemical product is lotion or cream.
[0017] In some embodiments, the daily chemical is a pearlescent hair dye; by weight percentage, the pearlescent hair dye also includes 0.1-2% disodium EDTA, 0.1-2% sodium sulfite, 0.1-2% sodium isoascorbate, an appropriate amount of color powder, 1-20% liquid crystal emulsified complex, 0.1-5% non-ionic emulsifier, 5-10% cetearyl alcohol, 0.1-2% oleyl alcohol, 2-10% pearlescent agent ethylene glycol distearate, 0.5-0.8% aminoethylaminopropyl polydimethylsiloxane, 1-2% polydimethylsiloxane, 2-4% cyclopentasiloxane, 1-10% monoethanolamine, 3-8% ammonium hydroxide, 0.5-5% sodium carbonate salt / ammonium salt, 0.1-5% fragrance, and the balance water.
[0018] The aminoethylaminopropyl polydimethylsiloxane, polydimethylsiloxane and cyclopentasiloxane as conditioning agents can give the hair a smooth and soft touch, reduce friction between the hair, thereby reducing hair damage and breakage, and prevent the hair from becoming dry, losing luster and elasticity due to hair dyeing. It can also form a protective film on the surface of the hair, which helps to maintain the moisture and nutrition of the hair, reduce the damage to the hair caused by the external environment, and thus reduce the damage to the hair caused by hair dyeing.
[0019] In some embodiments, the nonionic emulsifier is one or more of oleth-10, oleth-15, oleth-20, and oleth-30.
[0020] In some embodiments, the preparation method of the daily chemical comprises:
[0021] (1) Add water, disodium EDTA, sodium isoascorbate, sodium sulfite, color powder, and liquid crystal emulsified complex into an emulsifying pot and dissolve them and start heating;
[0022] (2) adding nonionic emulsifier, cetearyl alcohol, oleyl alcohol, and pearlescent agent ethylene glycol distearate into an oil phase pot and heating to melt;
[0023] (3) Heat the emulsification pot to 75°C. After all the materials in the oil phase pot are melted, add the raw materials in the oil phase pot into the emulsification pot and homogenize and emulsify for 3 minutes while keeping stirring;
[0024] (4) cooling to 65-55° C., adding monoethanolamine, aminoethylaminopropyl polydimethylsiloxane, polydimethylsiloxane, and cyclopentasiloxane and stirring;
[0025] (5) Cooling to 55-45°C, adding sodium carbonate / ammonium salt and ammonium hydroxide and stirring;
[0026] (6) When the temperature drops to 45°C, add the essence and stir for 15 to 25 minutes to obtain the pearlescent hair dye.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] According to the present invention, oleyl alcohol polyether and P2O5 undergo an esterification reaction in a water-containing reactor, and the product is hydrolyzed and then mixed with sodium oleyl alcohol polyether sulfate, sodium stearyl alcohol sulfate, and MEA salt / ammonium salt of oleic acid to obtain a liquid crystal emulsified composite. The liquid crystal emulsified composite is used for preparing emulsions and creams, can form a stable and uniform liquid crystal phase, effectively improves the stability of the product, can prevent aggregation and stratification, and can also control the gradual release of active ingredients.
[0029] At the same time, the present invention uses the liquid crystal emulsified composite to prepare a pearlescent hair dye cream, which has a simple preparation method and can be industrially produced on a large scale. The intermediate / coupling agent of the dye cream is separated from the alkali agent and the oxidant mainly by the multi-layer structure characteristics of the water-based liquid crystal technology, so that the oxidation reaction does not occur prematurely to form a macromolecular pigment, which helps the intermediate / coupling agent to penetrate into the hair, significantly improving the brightness, saturation and durability of the dyed hair color, and the paste is fine, pearlescent, moderately viscous and easy to blend with hydrogen peroxide, which improves the adhesion of the paste to the hair and is beneficial to the application of the hair dye cream. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solution of the present invention, the drawings required for use in the implementation mode will be briefly introduced below. Obviously, the drawings described below are only some implementation modes of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 This is a liquid crystal structure diagram of the pearlescent hair dye prepared by the liquid crystal emulsified composite in Example 4.
[0032] Figure 2 This is a liquid crystal structure diagram of the pearlescent hair dye prepared by the liquid crystal emulsified composite in Example 4.
[0033] Figure 3 The liquid crystal structures of the pearlescent hair dye prepared by the liquid crystal emulsified composite in Example 4 after being placed at 45° C. and 2° C. for 6 months and 1 year, respectively.
[0034] Figure 4 The photos are actual photos of the hair effects after dyeing with the pearlescent hair dye cream prepared with the liquid crystal emulsified composites of Examples 1 to 4 and Comparative Examples 1 to 2.
[0035] Figure 5 This is a graph analyzing the color values of hair after dyeing with the pearlescent hair dye cream prepared with the liquid crystal emulsified composites of Examples 1 to 4 and Comparative Examples 1 to 2.
[0036] Figure 6 The figure is an analysis chart of the color durability of hair dyed with the pearlescent hair dye prepared with the liquid crystal emulsified composites of Examples 1 to 4 and Comparative Examples 1 to 2 after 1, 2, and 4 washes respectively.
[0037] Figure 7 The figure is an analysis chart of the color durability of hair dyed with the pearlescent hair dye prepared with the liquid crystal emulsified composites of Examples 1 to 4 and Comparative Examples 1 to 2 after 6, 8, and 10 washes, respectively.
[0038] Figure 8 These are actual photos of the pearlescent hair dye cream prepared by the liquid crystal emulsified composite of Example 4 and Comparative Example 2. DETAILED DESCRIPTION
[0039] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0041] In the present invention, there is no particular limitation on the specific dispersion and stirring treatment methods.
[0042] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.
[0043] Preparation Example 1
[0044] A method for preparing a liquid crystal emulsified composite, the method comprising the following steps:
[0045] 1. At room temperature, add oleth-5 quantitatively into the esterification kettle containing deionized water, and the deionized water is 2% of the total reactants by mass.
[0046] 2. Raise the temperature to the feeding temperature and maintain the temperature, then slowly add P2O5 at a molar ratio of n(oleyl alcohol polyether-5):n(P2O5)=2.8:1.2, the feeding time is 50 min, the feeding temperature is 93°C, the esterification reaction temperature is 95°C, and the esterification reaction time is 2 h; at the same time, introduce nitrogen protection.
[0047] 3. After the esterification reaction is completed, hydrolysis is carried out by steam hydrolysis method, with a hydrolysis time of 0.5 h and a hydrolysis temperature of 70° C. to obtain an oleyl alcohol polyether phosphate product with high monoester content and low color.
[0048] 4. The oleyl alcohol polyether phosphate obtained in step 3 was mixed with sodium oleyl alcohol polyether sulfate, sodium stearyl alcohol sulfate, and MEA / ammonium coconut oil salt in a mass ratio of 35:30:5:20, and heated at 76° C. and stirred at 1200 rpm to form a paste to obtain a liquid crystal emulsified composite. The paste viscosity was 23000 mPa.s (4# rotor / 6 rpm).
[0049] Preparation Example 2
[0050] A method for preparing a liquid crystal emulsified composite, the method comprising the following steps:
[0051] 1. At room temperature, add oleth-8 quantitatively into the esterification kettle containing deionized water, and the deionized water is 2% of the total reactant mass ratio.
[0052] 2. Raise the temperature to the feeding temperature and maintain the temperature, then slowly add P2O5 at a molar ratio of n(oleyl alcohol polyether-8):n(P2O5)=2.8:1.2, the feeding time is 40 min, the feeding temperature is 120°C, the esterification reaction temperature is 125°C, and the esterification reaction time is 4 h; at the same time, introduce nitrogen protection.
[0053] 3. After the esterification reaction is completed, hydrolysis is carried out by steam hydrolysis method, with a hydrolysis time of 0.5 h and a hydrolysis temperature of 85° C. to obtain an oleyl alcohol polyether phosphate product with high monoester content and low color.
[0054] 4. The oleyl alcohol polyether phosphate obtained in step 3 was mixed with sodium oleyl alcohol polyether sulfate, sodium stearyl alcohol sulfate, and MEA / ammonium coconut oil in a mass ratio of 45:20:15:30, and heated at 75° C. and stirred at 1300 rpm to form a paste to obtain a liquid crystal emulsified composite. The paste viscosity was 18000 mPa.s (4# rotor / 6 rpm).
[0055] Preparation Example 3
[0056] A method for preparing a liquid crystal emulsified composite, the method comprising the following steps:
[0057] 1. At room temperature, add oleth-20 quantitatively into the esterification kettle containing deionized water, and the deionized water is 2% of the total reactants by mass.
[0058] 2. Raise the temperature to the feeding temperature and maintain the temperature, then slowly add P2O5 at a molar ratio of n(oleyl alcohol polyether-20):n(P2O5)=1.8:0.6, the feeding time is 70 min, the feeding temperature is 85°C, the esterification reaction temperature is 95°C, and the esterification reaction time is 2 h; at the same time, introduce nitrogen protection.
[0059] 3. After the esterification reaction is completed, hydrolysis is carried out by steam hydrolysis method, the hydrolysis time is 2h, and the hydrolysis temperature is 70°C; an oleyl alcohol polyether phosphate product with high monoester content and low color is obtained.
[0060] 4. The oleyl alcohol polyether phosphate obtained in step 3 is mixed with sodium oleyl alcohol polyether sulfate, sodium stearyl alcohol sulfate, and MEA / ammonium coconut oil salt in a mass ratio of 35:30:5:20, and heated at 78° C. and stirred at 1000 rpm to form a paste to obtain a liquid crystal emulsified composite. The paste viscosity is 25000 mPa.s (4# rotor / 6 rpm).
[0061] Preparation Example 4
[0062] A method for preparing a liquid crystal emulsified composite, the method comprising the following steps:
[0063] 1. At room temperature, add oleth-5 quantitatively into the esterification kettle containing deionized water, and the deionized water is 2% of the total reactants by mass.
[0064] 2. Raise the temperature to the feeding temperature and maintain the temperature, then slowly add P2O5 at a molar ratio of n(oleyl alcohol polyether-5):n(P2O5)=2.4:0.9, the feeding time is 50 min, the feeding temperature is 93°C, the esterification reaction temperature is 102°C, and the esterification reaction time is 3 h; at the same time, introduce nitrogen protection.
[0065] 3. After the esterification reaction is completed, hydrolysis is carried out by steam hydrolysis method, with a hydrolysis time of 1 hour and a hydrolysis temperature of 82° C. to obtain an oleyl alcohol polyether phosphate product with high monoester content and low color.
[0066] 4. The oleyl alcohol polyether phosphate obtained in step 3 was mixed with sodium oleyl alcohol polyether sulfate, sodium stearyl alcohol sulfate, and MEA / ammonium coconut oil salt in a mass ratio of 40:25:10:25, and heated at 76° C. and stirred at 1200 rpm to form a paste to obtain a liquid crystal emulsified composite. The paste viscosity was 20000 mPa.s (4# rotor / 6 rpm).
[0067] Examples 1 to 4 and Comparative Examples 1 to 2
[0068] 1. A pearlescent hair dye containing a liquid crystal emulsified complex, made from the components in the mass percentages shown in Table 1 below:
[0069] Table 1 Pearlescent hair dye formula of Examples 1 to 4 and Comparative Examples 1 to 2
[0070]
[0071]
[0072] In the table, Examples 1 to 4 are liquid crystal emulsified composites prepared in Preparation Examples 1 to 4, respectively.
[0073] 2. A method for preparing a pearlescent hair dye cream containing a liquid crystal emulsified complex, according to the formula in Table 1 above, the preparation method comprises the following steps:
[0074] 1. Add water into an emulsifying pot, add propylene glycol, disodium EDTA, sodium isoascorbate, sodium sulfite, toner, and liquid crystal emulsified complex (Comparative Examples 1 to 2 do not add liquid crystal emulsified complex, and cationic emulsifier 1831 and monoglycerol stearate are used) into the emulsifying pot to dissolve and start heating;
[0075] 2. Add oleth-30, oleth-10, cetearyl alcohol, oleyl alcohol, and pearlescent agent ethylene glycol distearate into the oil phase pot and heat to melt;
[0076] 3. Heat the emulsification pot to 75°C. After all the materials in the oil phase pot are melted, pump the oil in the oil phase pot into the emulsification pot, homogenize and emulsify for 3 minutes, keep stirring, and start cooling;
[0077] 4. When the temperature drops to 60°C, add monoethanolamine, aminoethylaminopropyl polydimethylsiloxane, polydimethylsiloxane and cyclopentasiloxane and keep stirring.
[0078] 5. When the temperature drops to 50°C, add sodium carbonate / ammonium salt and ammonium hydroxide and keep stirring.
[0079] 6. When the temperature drops to 45°C, add the essence and stir for 15 to 25 minutes until the mixture is evenly mixed.
[0080] Test Example 1
[0081] 1. Use polarizing microscope to observe the liquid crystal emulsion structure and observe the liquid crystal structure stability of the emulsion over a period of time.
[0082] 2. Use virgin black hair of the same chromaticity for dyeing, sensory evaluation and CIE Lab color testing.
[0083] 2.1 Sensory evaluation: The dyed hair bundles were placed in a constant temperature and humidity chamber for 12 hours to dry, and then taken out for comparative observation.
[0084] 2.2 Before dyeing the hair, measure the L, a, and b values of the original black hair, and use the bright red dye formula of color number 7 / 45 for hair dyeing. After dyeing, place the hair bundles in a constant temperature and humidity chamber for 12 hours to dry, measure the L, a, and b values again, calculate the ΔL, Δa, and Δb values, and then calculate ΔE using formula (1).
[0085]
[0086] The larger the ΔE, the greater the color difference, indicating a higher degree of hair color change;
[0087] The larger the ΔL, the greater the degree of change in color depth. At the same time, according to the L, a, and b color theory, the a value represents the red and green value. The larger the a value, the redder the color, and the smaller the a value, the greener the color. Therefore, the larger the a value after dyeing, the more saturated and brighter the red color is.
[0088] 3. The color fading experiment of permanent hair dye was conducted using a 3NH colorimeter to test and compare the color difference of the dyed hair after the treatment of the present invention, and the ΔL, Δa, and Δb values were calculated and represented by the color difference symbol ΔE. ΔE is defined as the total color difference of the sample. The larger the ΔE value, the greater the color difference and the lower the color protection. The color difference calculation formula is as shown in the above formula (1).
[0089] After multiple washes, the larger the ΔE, the greater the color difference, which means the hair color has faded more and the color durability is worse; the smaller the ΔE, the smaller the color difference, which means the hair color has faded less and the color durability is better.
[0090] Result analysis:
[0091] Depend on Figures 1-2 It can be seen that the pearlescent hair dye prepared by the liquid crystal emulsified composite of the present invention can form a uniformly distributed and complete liquid crystal structure. Figure 3 It can be seen that the pearlescent hair dye made from the liquid crystal emulsion composite of the present invention can remain stable after being placed for 6 months or 1 year under different environmental conditions (45°C or 2°C), indicating that its liquid crystal structure will not be easily destroyed or disappear due to changes in external conditions and has good stability.
[0092] Depend on Figures 4 to 7 It can be seen that compared with Comparative Examples 1 to 2, the degree of color change of the hair after dyeing with the pearlescent hair dye prepared by the liquid crystal emulsion composite of Examples 1 to 4 is relatively high, indicating that the liquid crystal emulsion composite of Examples 1 to 4 can significantly promote the penetration of color powder and significantly improve the color saturation, brightness and vividness, especially the liquid crystal emulsion composite prepared in Example 4 has the highest degree of color change.
[0093] Then in the color durability experiment, the hair dyed with the pearlescent hair dye prepared with the liquid crystal emulsion composites of Examples 1 to 4 had a small color difference after being washed 1, 2, 4, 6, 8, and 10 times, respectively, indicating that the liquid crystal emulsion composites of Examples 1 to 4 can enhance the adhesion of the paste to the hair, thereby improving the color durability.
[0094] Depend on Figure 8 It can be seen that the pearlescent hair dye cream of the present invention has a strong appearance and moderate paste viscosity.
[0095] In summary, the present invention allows oleyl alcohol polyether to undergo an esterification reaction with P2O5, and the product is hydrolyzed and then mixed with sodium oleyl alcohol polyether sulfate, sodium stearyl sulfate, and MEA salt / ammonium salt of oleic acid to obtain a liquid crystal emulsion composite, which can be used as an additive in daily chemicals (especially permanent hair dye products) and can significantly enhance the color saturation and color durability of hair dye products.
[0096] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a liquid crystal emulsified composite for promoting toner penetration, characterized in that: The preparation method comprises the following steps: S1. Under inert gas, oleyl alcohol polyether and P2O5 are esterified in a water-containing reactor at 95 to 125 ° C for 2 to 4 hours, wherein the water is 2% of the total reactants by mass; S2. After the esterification reaction is completed, hydrolyze at 70-85° C. for 0.5-2 h to obtain oleyl alcohol polyether phosphate; S3. Mix the oleyl alcohol polyether phosphate, sodium oleyl alcohol polyether sulfate, sodium stearyl alcohol sulfate, and MEA oleate / ammonium salt in a mass ratio of (35-45):(20-30):(5-15):(20-30), heat and stir evenly to obtain a liquid crystal emulsified composite.
2. The method for preparing a liquid crystal emulsified composite for promoting toner penetration according to claim 1, characterized in that: In step S1, the oleth is one or more of oleth-5, oleth-8, oleth-10 and oleth-20.
3. The method for preparing a liquid crystal emulsified composite for promoting toner penetration according to claim 1, characterized in that: In step S1, oleyl alcohol polyether is first added into a reaction kettle containing water, and then the temperature is raised to 85-120° C. and P2O5 is slowly added thereto, with the addition time being 40-70 min.
4. The method for preparing a liquid crystal emulsified composite for promoting toner penetration according to claim 1, characterized in that: In step S1, the molar ratio of oleyl alcohol polyether to P2O5 is (1.8-2.8):(0.6-1.2).
5. The method for preparing a liquid crystal emulsified composite for promoting toner penetration according to claim 1, characterized in that: In step S1, the molar ratio of oleyl alcohol polyether to P2O5 is 2.4:0.
9.
6. The method for preparing a liquid crystal emulsified composite for promoting toner penetration according to claim 1, characterized in that: In step S3, the mass ratio of oleyl alcohol polyether phosphate, oleyl alcohol polyether sodium sulfate, sodium stearyl alcohol sulfate, and oleic acid MEA salt / ammonium salt is 40:25:10:
25.
7. A daily chemical product, characterized in that: The invention comprises a liquid crystal emulsified composite prepared by the preparation method according to any one of claims 1 to 6.
8. The daily chemical product according to claim 7, characterized in that: The daily chemical product is a pearlescent hair dye; in terms of weight percentage, the pearlescent hair dye also includes 0.1-2% disodium EDTA, 0.1-2% sodium sulfite, 0.1-2% sodium isoascorbate, an appropriate amount of color powder, 1-20% liquid crystal emulsified complex, 0.1-5% nonionic emulsifier, 5-10% cetearyl alcohol, 0.1-2% oleyl alcohol, 2-10% pearlescent agent ethylene glycol distearate, 0.5-0.8% aminoethylaminopropyl polydimethylsiloxane, 1-2% polydimethylsiloxane, 2-4% cyclopentasiloxane, 1-10% monoethanolamine, 3-8% ammonium hydroxide, 0.5-5% sodium carbonate salt / ammonium salt, 0.1-5% essence, and the balance water.
9. The daily chemical product according to claim 8, characterized in that: The nonionic emulsifier is one or more of oleth-10, oleth-15, oleth-20 and oleth-30.
10. The daily chemical product according to claim 8, characterized in that: The preparation method of the daily chemical product comprises: (1) Add water, disodium EDTA, sodium isoascorbate, sodium sulfite, color powder, and liquid crystal emulsified complex into an emulsifying pot and dissolve them and start heating; (2) adding nonionic emulsifier, cetearyl alcohol, oleyl alcohol, and pearlescent agent ethylene glycol distearate into an oil phase pot and heating to melt; (3) Heat the emulsification pot to 75°C. After all the materials in the oil phase pot are melted, add the raw materials in the oil phase pot into the emulsification pot and homogenize and emulsify for 3 minutes while keeping stirring; (4) cooling to 65-55° C., adding monoethanolamine, aminoethylaminopropyl polydimethylsiloxane, polydimethylsiloxane, and cyclopentasiloxane and stirring; (5) Cooling to 55-45°C, adding sodium carbonate / ammonium salt and ammonium hydroxide and stirring; (6) When the temperature drops to 45°C, add the essence and stir for 15 to 25 minutes to obtain the pearlescent hair dye.
Citation Information
Cited By
Ammonia-free dye paste and preparation method thereof
CN121242972A